2014
DOI: 10.1017/s0317167100016620
|View full text |Cite
|
Sign up to set email alerts
|

The Portrayal of Tourette Syndrome in Film and Television

Abstract: 226Gilles de la Tourette's syndrome (TS) is a neuropsychiatric disorder characterized by recurrent motor and vocal tics for at least one year 1 . Tourette's syndrome has a prevalence of 0·4% to 3·8% in children aged 5 to 18 years 2 , with peak severity between the ages of 8 to 12 3 . Common co-morbidities include attention deficit hyperactivity disorder (ADHD) 4 , learning disabilities 5 , and obsessive compulsive disorder (OCD) 6 . The etiology of TS is unknown, and as such, its symptoms are often misdiagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…In popular cultural portrayals the accuracy of symptomology has been wilfully abandoned and extreme cases of TS have prevailed over the typical ones. The participants’ stereotypical recollections of images of TS in the media are consistent with the findings of a recent study (Calder-Sprackman et al 2014) which demonstrated that Tourette’s is used in films and television to exonerate the use of profanities and entertain the audience. Thus, for comic effect, Tourette’s syndrome has been presented as the ‘swearing disorder’ where as in fact although coprolalia can be encountered in individuals with TS, only a minority is afflicted.…”
Section: Discussionsupporting
confidence: 88%
“…In popular cultural portrayals the accuracy of symptomology has been wilfully abandoned and extreme cases of TS have prevailed over the typical ones. The participants’ stereotypical recollections of images of TS in the media are consistent with the findings of a recent study (Calder-Sprackman et al 2014) which demonstrated that Tourette’s is used in films and television to exonerate the use of profanities and entertain the audience. Thus, for comic effect, Tourette’s syndrome has been presented as the ‘swearing disorder’ where as in fact although coprolalia can be encountered in individuals with TS, only a minority is afflicted.…”
Section: Discussionsupporting
confidence: 88%
“…Tourette's is also a syndrome that has mostly been misunderstood by the public and mocked by the media [24,25]. The stereotypical image of a person with unpredictable and unstable behaviour who has the irresistible urge to utter obscenities has been perpetuated within popular culture through comedic films like "Not another Teen movie".…”
Section: Stigma and Tourette's Syndromementioning
confidence: 99%
“…The condition has been portrayed as the 'swearing disease' within mainstream media (Calder-Sprackman et al, 2014;Fat et al, 2012) by virtue of the symptom of coprolalia (involuntary utterances of obscene words), although this feature of TS is fairly uncommon (Freeman et al, 2009). It has also been rendered as synonymous with unpredictable behaviour (Malli et al, 2016) and it has served as a pretext by a number of public figures within the entertainment industry and the political arena to hurl insults and offensive statements with impunity.…”
Section: Introductionmentioning
confidence: 99%